2020
DOI: 10.1093/braincomms/fcaa015
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of HIV and ageing on neural oscillations: independence from neuropsychological performance

Abstract: HIV infection is associated with increased age-related co-morbidities including cognitive deficits, leading to hypotheses of HIV-related premature or accelerated ageing. Impairments in selective attention and the underlying neural dynamics have been linked to HIV-associated neurocognitive disorder; however, the effect of ageing in this context is not yet understood. Thus, the current study aimed to identify the interactive effects of ageing and HIV on selective attention processing. A total of 165 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
3
13
0
Order By: Relevance
“…In contrast, PWH exhibited a different trajectory of prefrontal theta activity with increasing age, as young PWH showed stronger theta responses on invalid relative to valid trials, but with increasing age this pattern reversed and PWH responded equally or slightly more strongly to valid trials. To our knowledge, this is the first study of attentional reorienting in PWH, but it should be noted that other studies have found prefrontal theta aberrations in the context of cognitive interference [31] and ageing [33] in PWH. Further, such reports of theta aberrations in PWH have not been limited to the prefrontal cortices [ 37 , 39 ].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In contrast, PWH exhibited a different trajectory of prefrontal theta activity with increasing age, as young PWH showed stronger theta responses on invalid relative to valid trials, but with increasing age this pattern reversed and PWH responded equally or slightly more strongly to valid trials. To our knowledge, this is the first study of attentional reorienting in PWH, but it should be noted that other studies have found prefrontal theta aberrations in the context of cognitive interference [31] and ageing [33] in PWH. Further, such reports of theta aberrations in PWH have not been limited to the prefrontal cortices [ 37 , 39 ].…”
Section: Discussionmentioning
confidence: 70%
“…1 ), including 51 unimpaired PWH (mean age = 47.82, 20 females), 28 impaired PWH (i.e., HAND; mean age = 47.04, 10 females), and 94 unimpaired HIV-negative controls (mean age = 45.60, 42 females). Based on previous relevant studies from our laboratory and others [ 31 , 33 , 35 , 37 , 76 , 77 ], we had a reasonable sample size per group for both behavioral and neural comparisons. Participants completed a neuropsychological battery assessing multiple functional domains, including attention [WAIS-III Symbol Search [78] and Stroop Word [79] ], speed of processing [Trail Making Part A [15] , WAIS-III Digit Symbol, and Stroop color], executive functioning [Trail Making Part B, Stroop interference, phonemic verbal fluency and semantic verbal fluency [80] ], fine motor [grooved pegboard [ 80 , 81 ]], verbal learning and memory [Hopkins Verbal Learning Test–Revised [82] ] and language [Wide Range Achievement Test-4th edition [83] , Word Reading subtest].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visuospatial processing is a central component of many higher order cognitive processes, and along with attention function is among the most common cognitive impairments observed in PWH (Antinori et al, 2007; Gorman, Foley, Ettenhofer, Hinkin, & van Gorp, 2009; Masters & Ances, 2014; Woods, Moore, Weber, & Grant, 2009). To interrogate the origin of these neuropsychological impairments, spatially precise brain imaging technologies such as magnetoencephalography (MEG) and structural and functional magnetic resonance imaging (sMRI/fMRI) have been used (Lew et al, 2021; Masters & Ances, 2014), and several studies have reported neural alterations in PWH, both inherent and related to visuospatial processing and attention function (Babiloni et al, 2012, 2014; Groff et al, 2020; Lew et al, 2018, 2020; Wiesman et al, 2018; Wilson et al, 2013). For example, fMRI studies of attention processing among PWH have shown decreases in parietal attention network regions compared with controls (Chang et al, 2004), and increases in prefrontal regions as a function of attention load (Chang, Yakupov, Nakama, Stokes, & Ernst, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These studies also found increased pre‐stimulus neural activity in the same brain regions serving visuospatial and attention processing, such that cognitively impaired and unimpaired PWH showed elevated theta, alpha, and gamma during the pre‐stimulus periods (Lew et al, 2018; Wiesman et al, 2018). Such altered neural oscillations and elevated pre‐stimulus neural activity have often been associated with concomitant impairments in task performance (e.g., Heinrichs‐Graham & Wilson, 2016; Lew et al, 2018, 2020; McDermott et al, 2019; Wiesman et al, 2018). Theta power has been strongly linked to initial stimulus registration and initialization and termination of attentional selection from one stimulus to another (Busch, Dubois, & VanRullen, 2009; Fries, 2015; Landau & Fries, 2012; Landau, Schreyer, van Pelt, & Fries, 2015), while alpha has been linked to the active inhibition of distracting visual input, often in the context of attention and/or working memory paradigms (Wiesman, Groff, & Wilson, 2019).…”
Section: Introductionmentioning
confidence: 99%